Meeting the needs of Generation Z Latinx community college students - Airhart, Alison (Kansas State University, 2022)
Generation Z, individuals born between 1995 and 2010, is projected to soon be the first minority-majority generation in the United States. This generational cohort is attending colleges now and will continue to enter colleges for the next decade. Within the Generation Z population are a large group of the Latinx students who often struggle to meet their educational goals. Exploring the needs of Generation Z Latinx students will help college leaders understand how best to serve this population. Information is becoming widespread on Generation Z as a whole, but research that examines the Generation Z Latinx student is still limited. Data related to the educational barriers and supports, and services needed by Generation Z Latinx students attending a California community college was collected to understand how community colleges can better serve this population and help them progress toward their educational goals. The purpose of this study was to discover what barriers are preventing this cohort from reaching their educational goals and what supports are needed to help improve this populations’ educational outcomes. Using a mixed-methods case study to uncover the needs of Generation Z Latinx community college students, this study offers insights on how colleges can best serve this student population. Results of this study offer perceptions from data collection, surveys, and focus group interviews on what are the social, financial, instructional, and cultural needs of these students.
Keywords: Generation Z; Gen Z; Latinx; Hispanic; Community college students; Postsecondary education; HSIs